Assessment of re-entry survivability of aluminum oxide with different nanostructures considering surface catalytic heat-transfer - Seong-Hyeon Park; Yosheph Yang; Ikhyun Kim (Case Studies in Thermal Engineering, 2024)
Re-entry survivability analysis is generally performed with the assumption of a smooth surface, for which the effect of surface roughness can be ignored. In such an approach, analysis may not provide accurate estimation of the survivability analysis of the re-entry object. The material surface roughness is known to enhance the surface catalytic properties of the material and thus results in a higher heat transfer. The present work incorporates the influence of surface roughness into the re-entry analysis in terms of surface catalytic recombination efficiency. The material catalytic efficiency value is obtained by using catalytic heat transfer theory in the shock tube end-wall heat transfer measurement. The material considered in the analysis is aluminum oxide with various levels of surface roughness. The roughness is varied by mechanical abrasion by using silicon carbide (SiC) sandpaper. The quality of the material is also assessed with different characterization techniques that include EDS, XPS, and AFM measurement. Through experimental measurement, it is observed that the surface catalytic recombination efficiency increases as the surface roughness level increases. Using the obtained efficiency values, the re-entry survivability analysis shows that a material with a high level of surface roughness exhibits a low survivability rate.